Study of Ovarian Masses in Young Females: A Hospital Based Study - Paul, B. J.; Lamsal, B.; Sinha, K.; Das, C. R. (Journal of Nepalgunj Medical College, 2017)
Objective: The purpose of this study was to analyze various clinical presentations, and the management of ovarian lesion in the young girls. Materials and methods: All the patients within the age limit of 20, who were admitted in the department of obstetrics and gynecology in NGMC between October 2011 to September 2015 with a diagnosis of an ovarian mass were analyzed. Age, presenting symptoms, duration of symptoms, physical examination findings and radiological imaging results were obtained. Ultrasonography was the gold standard for the diagnosis. The preliminary and final diagnoses were recorded. Results: 25 patients were identified, diagnosis of functional cyst was accounted for 9, 5 were hemorrhagic cyst and chocolate cyst and neoplastic tumors were accounted for 11 patients during the same period. The most common presenting complaint was abdominal pain. On physical examination 8 girls had abdominal tenderness and 15 patients had palpable masses. Conclusion: Ovarian masses presenting with abdominal complaint can mimic other diseases. Ultrasound examination is one of the most important diagnostic tools. Preoperative diagnostic approach of the patient includes careful history taking, physical examination, imaging and evaluation of biological markers in selective cases. Conservative surgery is advocated to preserve the fertility potential of these patients. JNGMC Vol. 13 No. 2 December 2015, Page: 38-41